CERTAIN PECULIARITIES OF THE SYSTEM OF MUNICIPAL FINANCE CONTROL IN THE RUSSIAN FEDERATION - Vitaliy I. Perov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes expert work as a method of finance control and information function imbedded in it. It was shown that functioning of the municipal finance control system could lead to raising efficiency and effectiveness of local self-government bodies. The author offers recommendations aimed at enhancing normative acts regulating the activity of the municipal finance control system and raising the efficiency of local self-government bodies' work. The contribution of the municipal finance control system to the social and economic development of territories was analyzed.